Copula-based vMEM specifications versus alternatives: The case of trading activity - Fabrizio Cipollini; Robert F. Engle; Giampiero M. Gallo (Econometrics, 2017)
We discuss several multivariate extensions of the Multiplicative Error Model to take into account dynamic interdependence and contemporaneously correlated innovations (vector MEM or vMEM). We suggest copula functions to link Gamma marginals of the innovations, in a specification where past values and conditional expectations of the variables can be simultaneously estimated. Results with realized volatility, volumes and number of trades of the JNJ stock show that significantly superior realized volatility forecasts are delivered with a fully interdependent vMEM relative to a single equation. Alternatives involving log-Normal or semiparametric formulations produce substantially equivalent results.
Keywords: C32; C53; C58; 330; GARCH; MEM; realized volatility; trading volume; trading activity; trades; copula; volatility forecasting